Main Characteristics of the Japanese Studies Programme at the University of Ljubljana and Historical contingencies That Shaped It - Bekeš, Andrej (Acta Orientalia Vilnensia, 2005)
University of Ljubljana Faculty of Arts The Japanese Studies programme at the Faculty of Arts, University of Ljubljana has been established on October 1, 1995. Its main characteristics are: 1) a double major programme with a possibility to combine it with about 60 other double major programmes in humanities and social sciences, 2) openness, with 50–55 students enrolled every year and with Japanese language courses for non-specialists, 3) in close co-operation with the Chinese Studies programme, a wider East Asian perspective, 4) lively international exchange based on co-operation agreements with several major Japanese universities. These characteristics are the result of historical contingencies, necessity and available possibilities. With the curricular reform along the Bologna guidelines, a possibility for further improvement has been offered.